ACUTE INFECTIOUS DIARRHEA IN CHILDREN - T.V. Kulichenko; M.D. Bakradze; Yu.S. Patrusheva (Педиатрическая фармакология)
The article highlights the key principles for detection and differentiation of the acute infectious diarrhea in children. The modern guidelines for treatment of the acute gastroenteritis and gastroenterocolitis are based on the rational application of the antibacterial medications and minimization drugs administration. There are therapeutic approaches recommended by WHO and ESPGHAN.Key words: acute gastroenteritis, gastroenterocolitis, diarrhea, acute enteric infections, detection, treatment, oral rehydration, nifuroxazide, children.